TENSILE AND FLEXURAL STRENGTH OF ENGINEERED CEMENTITIOUS COMPOSITE (ECC) INCORPORATING CRUMB RUBBER AND NANO SILICA - MUHAMMAD FIRDAUS, HUDA (IRC, 2019)
Engineered Cementitious Composites (ECC) presents enhancement on both ductility and tensile strain capability aspects whilst maintaining its high strength characteristic compared to conventional concrete. However, problems arise from ECC utilization was its fire resistance capability whenever exposed to significantly high temperature. This shows that addition of crumb rubber was crucial to hinder the development of internal tensile stress due to vapor pressure which proceeding cause spalling of concrete structure.